2011
DOI: 10.3354/esr00363
|View full text |Cite
|
Sign up to set email alerts
|

Use of radiotelemetry to track threatened dorados Salminus brasiliensis in the upper Uruguay River, Brazil

Abstract: Little is known about the seasonal movements of fish that inhabit large rivers in South America, which makes it difficult to identify potential threats to fish populations associated with the proliferation of hydropower developments. Dorados Salminus brasiliensis (Characiformes) are large riverine piscivores that are targeted by recreational and commercial fishers and are considered regionally 'vulnerable' in Brazil due to overfishing, pollution, and habitat fragmentation. Here, we used radio telemetry to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 19 publications
2
20
0
1
Order By: Relevance
“…The tag/signal loss rates of 16% (Godinho & Kynard, 2006), 19.5% (Andrade-Neto, 2008, 40.5% (Hahn et al, 2011), 18% (Silva, 2012), 20% (Ribeiro, 2013) and 10% (Suzuki, 2014) estimated in these studies are comparable to the complication rates (21%) observed in this study. Some of that loss may be attributed to adverse effects from surgical tagging, including tag expulsion and changes in behavior that may reduce movement rates or increase the chance of capture by fishermen, predation, or death of tagged individuals.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The tag/signal loss rates of 16% (Godinho & Kynard, 2006), 19.5% (Andrade-Neto, 2008, 40.5% (Hahn et al, 2011), 18% (Silva, 2012), 20% (Ribeiro, 2013) and 10% (Suzuki, 2014) estimated in these studies are comparable to the complication rates (21%) observed in this study. Some of that loss may be attributed to adverse effects from surgical tagging, including tag expulsion and changes in behavior that may reduce movement rates or increase the chance of capture by fishermen, predation, or death of tagged individuals.…”
Section: Discussionsupporting
confidence: 82%
“…Telemetry can remotely and precisely transfer information from tagged fish with a radio or acoustic transmitter across spatial and temporal scales to study the behavior of Neotropical freshwater fishes and their relationship with environmental variables (Koehn, 2012). In recent years, affordable technologies and an increase in the number of international collaborations with Brazilian research institutions have broadened the Brazilian regions covered by these studies from river basins in southern and southeastern states since the early 2000s (Godinho & Kynard, 2006;Schulz & Leuchtenberger, 2006;Alves et al, 2007;Godinho et al, 2007;Hahn et al, 2007;Andrade-Neto, 2008;Pesoa & Schulz, 2010;Hahn et al, 2011;Alves, 2012;Silva, 2012;Ribeiro, 2013;Pérez, 2014;Suzuki, 2014) to other large river basins in central and north regions of the country.…”
Section: Introductionmentioning
confidence: 99%
“…In saline environments, PSATs based on corrosive releases that enable tags to be jettisoned can be used In areas with human activity, some telemetry infrastructure is conspicuous and can attract vandals [48] Acoustic receivers, if deployed at depths and using gear that the public cannot easily reach, are usually safe from vandals Development of less conspicuous deployments for radio and PIT gear, such as autonomous underwater antennas and receiving systems (as is common in acoustic telemetry) Swim-through PIT loops, with the top edge above the water surface should not be deployed where boats occur Most fixed-radio and PIT tag antenna arrays (unless in controlled access areas) are subject to vandalism even when using 'vandal-resistant' gear Table 2 Summary of key constraints (categorized by abiotic, anthropogenic, environmental/habitat, and biotic) associated with using electronic tags to study animals in freshwater systems, existing technical solutions, and additional technical needs that need to be addressed to improve equipment performance and science outcomes (Continued) Satellite connections enable data to be retrieved and receivers to be configured from afar (already exists for radio [51] and recently developed for acoustic systems with a surface cable and GPS or cell interface)…”
Section: Stationary Trackingmentioning
confidence: 99%
“…Data about recapture of electronic tagged fish and return of transmitters by fishers has been reported in other biotelemetry projects in Brazil and ranged from 13 to 54% (Godinho and Kynard, 2006;Godinho et al, 2007;Hahn et al, 2011;Pesoa and Schulz, 2010), values that are greater than observed so far in the Xingu River. The return of transmitters is important because it not only makes it possible to reuse the tags in other fish, but also because fishers will provide information on the use of habitats beyond the limits of study area and after the transmitter battery runs out.…”
Section: Reporting On the Recapture Of Electronic Tagged Fish By Fishmentioning
confidence: 89%
“…The return of transmitters is important because it not only makes it possible to reuse the tags in other fish, but also because fishers will provide information on the use of habitats beyond the limits of study area and after the transmitter battery runs out. In the Uruguay River a tagged dourado (Salminus brasiliensis; Cuvier, 1818) was recaptured 300 km downstream of the study area after the monitoring was over (Hahn et al, 2011). In the Madeira River, a radio tagged dourada was recaptured by a fisher 150 km downstream of the study area (L. Hahn, personal observation).…”
Section: Reporting On the Recapture Of Electronic Tagged Fish By Fishmentioning
confidence: 99%